Math 26 - 9
Math 26 - 9
Math 26 - 9
"
ett )
My Lt ) = F- ( = E e
YER
Py (y )
d My Lt ) DE City)
" =
d
my ( t )
= F- ( Y ) "
dt dt
"
dt :O d- E "
py (y )
t =
e
at
YER
↳
=
yer
¥ e'
E Py (y )
"
= E ye Pylos )
DER
E
=
y Py(g) = F- ( Y)
YER
=
E
yer
¥ be
↳
by / g)
=
{ y2eᵗ↳ Pylos) / + =o
YER
= E y2 = C- (y2 )
DER
Q :
0; elsewhere
Find F- (
y)
solution .
.
E
Ely )=
YER
Y Py ly )
F- (4) = E is Pyly)
↳ = 1
a
=
E y (E) Y
y =L
}
=
It 2( E)2+3 ( t ) + 4 (E) 4- ..
.
=
{ (E) +
'
+ (1) 3T (E) % .
_
(f) 4.+
?
( É) (E)
'
+ + .
.
.
(E) %
'
(E) t . _.
(E) % .
.
3
= It É + (1)
2
+ (1)
=
1-
=
1- Y,
=
2
My Lt )= Ele ᵗY ) =
YER
E
eᵗ↳Py (g)
&
=
E ( { et )Y
y=l
My / t) -_
{ et + ( { et )2 +
( { et )
} 1-
( { et)4 , . .
.
1- { et
= ÷
et
=
2- et
|t=o
=
-
+
2
(z - et )
=
ll2;
= 2
11
ex 3-
let the random variable 4 have pmf Pylos ) given by
{ (3-9) 4=0 ,
, , z
{
,
Py / g) =
0 ; otherwise
=
É Y
•
¥13 -
y)
4=0
( et
"
melt ) = ± )
= E et" Py ly )
yep
=
É et"
% [ 3- 4)
y=0
§ ÷
2ᵗ
=
£ + et t
@
d^% / kettle /
"
=
+ =◦
+ = ,
=
↳ +
§
=
13
§ /
"
F- ( 42 ) et
=
t
5- e
c- =
↳ "ylt ) /
rn
to
◦
=
Is +
%
= I
'
V / 4) =
Elp ) 2- ( Elp ) ]
= I -
( -23 32
= I -
¥
=
¥
Binomial Drshibntron
In -9
(G) P ( I p ° 1
-
2
-
-
/ ,
,
- _ . -
, n
Pylos ) :
( o ; elsewhere
( atb )
"
=
E (1) an
-
K
b
"
K -0
-
↓
binomial
expansion
"
É P
"
( 1-b)
" →
that
(
shows
( Ip ) +p ) =
= , →
b. = 0 binomial is
valid
↑
4--1 p -
;
b =p
C- ( y ) : E spy lls )
y C-R
-9
)ⁿ
(1)
n "
P / i -
p
-
E y
5=0
h
yn ! Y
E pjn
-
☐
=
P ( 1-
9=0
¥ , ?
n.in?:::i::i-..
" "
b- '
=
E P p ( Ip )
"
É ,¥,;?→
" -
' n -
b
P Cup >
=np , ,
y= I
m
!
npgm.sn#pnCi-p)m-aN=0
m
E. (b) = np E
(1) pull
n
)m
-
p
E
-
-
_
np
n :O
=nPy
n
C- Ly
'
)= E 42 Py / y )
Yeo
=
E [ 4 + ycy -11JPY cos ]
9=0
n n
=
Ey Py (g) + Eycy - 1) Py 14 )
4=0 4=0
(G) pbli
-9
E bly 1)
-
p )n
(
-
9=0
s
=
§ blht) pbc , _
p ]
" -
D
b=o ↳ ! Cn -
y) !
n ph 2p2
-
→
= E y(y-l)n-Cn-1)ln- pls ( 1- pjn
-
Y
4=0 2) ? Cn 4) !
bly -1 ) ( y
-
-
n -2
( n -27 !
= nln 1) p2 E pls
-2
-
- n -
b
[1 -
p
]
4=2 ( g- 2)! (n y) !
-
let 2=9--2 ;
let men -2
' m
'
P2
=ncn
(Mn ) pnci
-
)m
n
[
-
-
p
h :O
= ncn - 1) p2
2
✓ ( Y ) : ECT
≥
) -
⇐ (
y) ]
= rip + pln - 1) P2 - ( np )
-
n' PZ n p 2- nap
2
up + -
= np -
np2
= n
(p - p2)
= n [ 1 -
p ]p
q=i p
npq
-
=
;